Antidiarrhoeal Activity of Dalbergia Sissoo Leaves in Goats - Amrutkar, Y. K.; Hajare, S.W.; Sontakke, A. R.; Bhojane, N. M.; Ingole, R. S.; lngawale , M. V. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
Antidiarrhoeal activity of Leaves of Dalbergia sissoo (D. sissoo) was evaluated in mice using castor  oil induced diarrhoea and gastrointestinal motility test with charcoal meal method and further in  clinical cases of goats. The results showed that the D. sissoo leaves extract (400 mg/kg and 800  mg/kg) produced significant (,o
Keywords: Antidiarrhoeal; Dalbergia sissoo; Castor oil; Charcoal; Mice; Goat